Understanding internationalization variance within a sport brand: case study of the Sparta Prague ice hockey and football clubs - Crossan, William; Šíma, Jan; Kaprálková, Michaela; Ruda, Tomáš (Frontiers in Sociology, 2024)
This article examines the internationalization of HC Sparta Prague (ice hockey) and AC Sparta Prague (football) by focusing on management decision-making. Using interviews with key personnel, it explores the varying levels of internationalization in these clubs, emphasizing their reliance on foreign players, the utility of foreign ownership, fan responses to foreign coaching, and marketing efforts toward foreigners. Football, being more global, is subject to ‘Europeanization,’ whereas ice hockey, centered in North America, is influenced by ‘Americanization’ and ‘eventification.’ Despite significant fan overlap and efforts at eventification, neither team has had success attracting Prague’s tourists and neither currently views it as an important market, instead focusing on the domestic Czech market. Both clubs have undergone various phases of ownership, from foreign investors to a return to Czech owners, reflecting broader social and economic changes in the region following the fall of communism. The article further discusses the influence of historical and cultural contexts on the acceptance and resistance to globalization influences, emphasizing the importance of preserving national identity and selectively integrating global elements within the modernization of sports. The study proposes that, despite the Sparta brand identity being heavily influenced by internationalization, it remains largely a Czech brand, and cultural sporting identity currently plays a more crucial role in resisting globalization than sport brand identity in Eastern Europe.